PROBLEM OF HEALTH SAVING OF SECONDARY SCHOOL STUDENTS IN TERMS OF ICT USE (Journal of Information Technologies in Education (ITE), 2015)
The last decade was marked by intensive development and introduction of new information and communication technologies, software and hardware into all spheres of human life. Besides the obvious positive effect (promoting efficiency, intensity, effectiveness, quality of education, etc.) use of these tools in children activities may lead to additional mental, nervous, emotional, physical,visual tension. However, compliance with certain pedagogical conditions can greatly reduce the negative impacts.     In the article the important aspects of health saving of secondary school pupils in conditions of ICT intensive implementation and use are considered. The benefits of these tools use, as well as potential threats to the health of the younger generation are outlined. The results of a survey of students (Kyiv, Poltava, Chervonyi Lutch) on their awareness about the basic requirements and standards of work with ICT, and their compliance are presented.     The purpose of the paper is in defining the main potential adverse effects that may result from using software and hardware on the health of the younger generation; determine the degree of awareness of secondary school pupils about these threats and ways to avoid them; representation of the possible ways to minimize negative impacts on pupils’ health.
Keywords: ICT; health saving; secondary school pupil; IC-competence